Analisis Yuridis Tindak Pidana Korupsi APBDES di Desa Percut Kecamatan Percut Sei Tuan - Hermansyah Siregar (Inovasi Pratama Internasional. Ltd, 2022)
It is often found that there are cases of misuse of APBDes carried out with various modus operandi. This study discusses how to regulate corruption offenses in Law Number 20 of 2001 concerning Criminal Acts of Corruption, how the criminal responsibility of perpetrators of corruption in the misuse of APBDes in Percut Village, Percut Sei Tuan District in the Indonesian Supreme Court Number 3313 K/Pid.Sus/2018 , what is the basis for the judge's consideration in making a decision against the defendant in the Decision of the Supreme Court of the Republic of Indonesia Number 3313 K/Pid.Sus/2018. The research method used is descriptive analysis that leads to normative juridical law research. The regulation of corruption offenses in Law Number 20 of 2001 concerning Corruption Crimes is Article 2 Paragraph (1) jo. Article 18 Paragraph (1) letter b of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. The criminal responsibility of the perpetrators of corruption in the misuse of APBDes in Percut Village, Percut Sei Tuan District in the Supreme Court of the Republic of Indonesia Number 3313 K/Pid.Sus/2018 is Chairil Anwar, SPd sentenced to prison for 4 (four) years and a fine of Rp.200,000,000 ( two hundred million rupiah). The basis of the judge's consideration in making a decision against the defendant in the Supreme Court of the Republic of Indonesia Number 3313 K/Pid.Sus/2018 by rejecting the appeal of the Public Prosecutor/Applicant for Cassation because the Court of Appeal in deciding the case was correct. Where in the trial the defendant's actions were in accordance with the legal facts and fulfilled all the elements in Article 2 paragraph (1) jo. Article 18 of Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption as amended by Law Number 20 of 2001 with a sentence of 4 (four) years in prison on the grounds that based on the facts in the trial that the Defendant was still carrying out the physical construction of drainage procurement Hamlet IX and Hamlet XI.